PEMANFAATAN RUANG DIGITAL SEBAGAI ALAT KOMUNIKASI BAGI PENGEMBANGAN USAHA EKONOMI WARGA - Taufik, Cevi Mochamad; Fitriawati, Diny; Aditya, Krisna; Ghassani, rizqi; Bintang, Gilang; Suhaeri; Sabarudin, Didin; Hasim; Wibowo, Edi; Suminar, Erna; Ahdi Widyaputra, Fauzan; Ati, Widia Sari Tresno; Sila, Gita Eka; Fikri, Miftakhul (LPPM UKRI, 2026)
The digital space can be utilized for various purposes. For empowerment goals, it can be used to enhance capabilities, improve quality, or boost community competencies. The same applies to business actors. The great benefits of the digital space are accessible to all without discrimination based on business scale or level—from conglomerate-class businesses, MSME-scale enterprises, to micro-level individual ventures, all have equal opportunities to leverage the digital space. Problems with digital tool usage arise when micro-level individual business actors remain unaware of the digital space's benefits. This is the background for the Community Service (PkM) activities conducted by lecturers and students from the Communication Science program at the National Republic of Indonesia University (Ilkom UKRI) in Madalajati Subdistrict, Bandung City. The PkM aims to provide knowledge and enhance skills for micro-sector business actors in accessibility and trading activities transformed into digital networks. To achieve this, the method used is lectures based on specific themes related to basic digital tool usage skills. PkM results show that residents' knowledge improved after receiving in-depth, comprehensive explanations on digitalization, and even commitments emerged to link their trading activities by first accessing digital networks